Indigenous entrepreneurship: a generator of social capital and respectful of the natural ecosystem - Tapia Mejía, Erik (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2023)
Entrepreneurship is considered a development strategy. The objective of this research is to discuss the importance of indigenous entrepreneurship in their localities and the relationship that these entrepreneurial impulses have with economic growth; for this purpose, a hermeneutic method is used with emphasis on the thematic literature on entrepreneurship in indigenous communities. The main results show that indigenous enterprises are creators of social capital and respectful of the natural ecosystem and add value by integrating in their products and/or services particular characteristics of their cultures, having successive activity in the primary production sectors.